Higher diagnostic value of metagenomic next-generation sequencing in acute infection than chronic infection: a multicenter retrospective study - Yao, Anjie; Wang, Jiale; Xu, Qintao; Shah, Binay Kumar; Sun, Kai; Hu, Feng; Wang, Changhui; Xie, Shuanshuan (Frontiers in Microbiology, 2024)
The aim of our study is to compare the metagenomic next-generation sequencing (mNGS) and conventional methods (CM), and explore different impacts of mNGS on chronic infection and acute infection. The multicenter retrospetive study showed the sensitivity and specificity of mNGS were higher than those of CM. There were significantly more patients changed antibiotic treatments in the mNGS positive group than mNGS negative group both in acute infection group. High levels of temperature, C-reactive protein, neutrophil and low levels of lymphocyte may lead to positive mNGS results in acute infection group while no factor was proved to predict positive results in chronic infection group. Thereefore, mNGS could provide useful guidance on antibiotic strategies in infectious diseases and may be more valuable for diagnosis and therapy in acute infection than these in chronic infection.